ENGEL FUZZY SUBGROUPS - Ameri, R.; Borzooei, R.A.; Mohammadzadeh, E. (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper we introduce and study Engel fuzzy subgroups. We will proceed by introduce and study soluble and nilpotent fuzzy subgroups. In particular, we show that if x ∈ L3(µ) and µ(x\(p^n\)) = µ(e) for some integer n ≥ 2, then µ is fuzzy soluble.